Introduksi Fermentasi Jerami Padi untuk Meningkatkan Produktivitas Ternak Sapi di Kelurahan Naioni, Kota Kupang: Introduction of Rice Straw Fermentation to Improve the Productivity of Cattle in Naioni Village, Kupang City - Randu, Melkianus Dedimus Same; Canadianti, Monica; Yuliani, Ni Sri; Anugrah, Dedet S. R.; Tabun, Arnold Christian; Wea, Redempta; Tulle, Defrys Ridolof (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  Rice straw fermentation is one of the feed technologies that can be utilized to reduce agricultural waste, improve feed quality, and increase the productivity of ruminants. Rice straw fermentation was introduced into the Community Science and Technology Implementation (PIM) program to optimize the utilization of agricultural waste for animal feed, mitigate pollution arising from burning, and enhance knowledge and technical expertise in feed processing. The implementation strategy involved a four-pronged approach: analyzing partner challenges, conducting counseling sessions and demonstration plots, providing ongoing mentorship, and implementing an evaluation and feedback loop. The PIM activities were implemented with the Ingat Aku farmer group in Naioni Village, Alak District, Kupang City. The results revealed positive changes in knowledge (3.57), attitude (4.79), and intention and behavior (4.57) of the farmer group members regarding the utilization of agricultural waste, specifically the production of fermented rice straw to support their existing paronisation activities.  Keywords: Feed technology; Fermentation; Paronisation   ABSTRAK Fermentasi jerami padi merupakan salah satu bentuk teknologi pakan yang dapat dimanfaatkan untuk mengurangi limbah pertanian, meningkatkan kualitas pakan, serta mempercepat peningkatan produktivitas ternak ruminansia. Fermentasi jerami padi yang diintroduksi dalam kegiatan Penerapan Iptek Masyarakat (PIM) bertujuan untuk mengoptimalkan pemanfaatan limbah pertanian sebagai pakan ternak, meminimalkan polusi akibat pembakaran, serta meningkatkan pengetahuan maupun keterampilan teknis dalam pengolahan pakan. Metode pelaksanaan diterapkan melalui analisis situasi permasalahan mitra, penyuluhan dan demonstrasi plot (demplot), pendampingan, serta evaluasi dan umpan balik. Kegiatan PIM dilaksanakan pada kelompok peternak Ingat Aku di Kelurahan Naioni, Kecamatan Alak, Kota Kupang. Hasil kegiatan menunjukkan perubahan terhadap aspek pengetahuan (3,57), sikap (4,79), serta niat dan perilaku (4,57) anggota kelompok peternak untuk memanfaatkan limbah pertanian khususnya hasil produksi fermentasi jerami padi dalam menunjang kegiatan paronisasi yang dilakukan saat ini. Kata kunci: Fermentasi; Paronisasi; Teknologi pakan